(3GdMhceI GdQTjOI aj GdLGeYGJ (B/s - (3Thedj, SgjQ GHQGgjes ((3YeGf(B: s (3OGQ GdGYUGQ GdYdej ddfTQ(B, s, 2016)
(3jVe GdMGcejI GdQTjOI,GSJQJjLjI GdJOQjH hGdJYdje Gdegfj hGdJbfj,GdSjGSGJ hGdELQGAGJ GdYGeI,GdMhceI GdeDSSjI,hGbY GdMhceI GdeDSSjI aj GdLGeYGJ hEWGQ GdHQfGeL GdebJQM,GdOhQ GdGLJeGYj hBaGb GdJYGhf,CKQ GdQjGOjI GdeYdheGJjI Ydi EOGQI GdeYQaIs
(3HjHdjhZQGajG(B: (3U(B.241-244s
Keywords: (3GdGOGQI GdJYdjejIs; (3GdLGeYGJ hGdcdjGJs